Clinical outcomes of lateral digital flap–based local flap combinations in the reconstruction of post-burn metacarpophalangeal joint contractures: Management of MP joint post-burn contractures - Melikoglu, Cenk (Journal of Surgery and Medicine, 2026)
Background/Aim: Post-burn metacarpophalangeal (MCP) joint contractures may severely impair hand function due to scar formation involving the palmar surface and volar digital skin. This study aimed to evaluate the clinical and functional outcomes of local flap combinations based on the lateral digital flap for the reconstruction of post-burn MCP joint contractures. Methods: This retrospective case series included nine male patients who underwent surgical treatment for post-burn MCP joint contractures between May 2010 and April 2011. A total of 48 local flaps were applied in various combinations according to contracture localization and defect characteristics. The lateral digital flap was used as the primary reconstructive method, rhomboid flaps were used for web space reconstruction, and five-flap Z-plasty was applied selectively for deformities involving the palmar surface and/or first web space. All flaps were designed before contracture release, and dissections were performed under tourniquet control with magnification. Clinical outcomes were assessed using postoperative extension deficit and follow-up duration (months). Results: All patients had contractures at the MCP joint level, with concomitant web space involvement in some cases. Complete restoration of MCP joint extension was achieved in eight patients. One patient had a 10° extension deficit localized to the proximal interphalangeal joint rather than the MCP joint. Follow-up ranged from 1 to 10 months. No flap loss or major postoperative complications were observed during follow-up. Conclusion: Local flap combinations based on the lateral digital flap constitute a biomechanically compatible, reliable, and functionally effective reconstructive option for post-burn MCP joint contractures in the early to mid-term period. In patients with multiple MCP joint contractures accompanied by web space deformities, combining the lateral digital flap with rhomboid flaps and/or five-flap Z-plasty allows comprehensive correction within a single surgical session.